VARIASI TUTUR PENERIMAAN DAN PENOLAKAN PEMBELI DALAM TRANSAKSI JUAL BELI BATIK DI PASAR GROSIR SETONO PEKALONGAN – KAJIAN SOSIOPRAGMATIK - Ika Arifianti (LPPM Universitas Pekalongan, 2012)
Communication is the most important aspect in human life whether in its process and social life of all people in the society. Communication is a process of sending information with its all aspects and effects. Therefore, language is the most important key to build the relation with others. There are two approaches used in this research; theoritical approach (using socio-pragmatic approach) and methodological approach (using qualitative approach). The result of this research shows that there are speech vatiations in buyer’s acceptance and refusal in Sentono wholesaler market in Pekalongan. They are direct acceptance speech and indirect acceptance speech. Direct acceptance speech is influenced by pragmatic effects such as interest, satisfaction, and symphaty. While indirect acceptance speech uses pragmatic functions such as (a) persuading, (b) urging, (c) convincing. There are also variations in direct and indirect refusal speech. Direct refusal uses expressions such as ‘ora’/’tidak’/’wis’/’tidak usah’/’oralah’/ ‘tidaklah’. While indirect refusal speech includes: (1) refusal without refusal expression, (2) refusal with interjection, (3) alternative refusal, (4) refusal with excuses.Keywords: speech variation, language, socio-pragmatics